2011
DOI: 10.2478/s11658-011-0019-7
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal sources of mesenchymal stem cells: Wharton’s jelly, amnion and chorion

Abstract: Recently, stem cell biology has become an interesting topic, especially in the context of treating diseases and injuries using transplantation therapy. Several varieties of human stem cells have been isolated and identified in vivo and in vitro. Ideally, stem cells for regenerative medical application should be found in abundant quantities, harvestable in a minimally invasive procedure, then safely and effectively transplanted to either an autologous or allogenic host. The two main groups of stem cells, embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 89 publications
0
61
0
2
Order By: Relevance
“…In four to five days, adhering spindle shape fibroblast-like cells resembling MSCs [28] began to appear. Supplemental Fig.…”
Section: Generation Of the Huadsc From Adipose Tissuementioning
confidence: 99%
“…In four to five days, adhering spindle shape fibroblast-like cells resembling MSCs [28] began to appear. Supplemental Fig.…”
Section: Generation Of the Huadsc From Adipose Tissuementioning
confidence: 99%
“…This can be used to isolate amniotic fluid MSC (AF-MSC) for genetic screening purposes. It has been found that amniotic fluid contains a heterogeneous population of many cells including a large portion of epithelioid E-type cells, amniotic fluid-specific AF-type cells and fibroblast F-type cells (Witkowska-Zimny andWrobel, 2011, Prusa andHengstschlager, 2002). Although many cell types exist within the amniotic fluid, MSC have been found.…”
Section: Amniotic Fluidmentioning
confidence: 99%
“…It has been estimated that approximately 1% of cells in culture obtained from human amniocentesis are MSC. Only a few studies have successfully isolated single cell-derived MSC clones from amniotic fluid (Tsai et al, 2004, De Coppi et al, 2007, Antonucci et al, 2009, Phermthai et al, 2010, Witkowska-Zimny and Wrobel, 2011.…”
Section: Amniotic Fluidmentioning
confidence: 99%
See 2 more Smart Citations